Quo Vadis, Völkerkundemuseum: Therapeutic Options for an Identity Crisis (KULT_online, 2016)
With their edited volume Quo Vadis, Völkerkundemuseum?, Michael Kraus and Karoline Noack ask the popular question of the ethnographic museum’s future. In the book, academic ethnologists enter into a dialogue with museum professionals in order to discuss the relation between universities and museums, institutional developments and new exhibition concepts.